Bioprospecção de espécies vegetais aromáticas da Amazônia Legal frente Aedes aegypti L. (DIPTERA: CULICIDAE): uma alternativa para o controle de arboviroses - LUZ, Tássio Rômulo Silva Araújo (2021)
In the world context, especially in tropical countries, arboviruses have become an important and constant threat to public health, especially those transmitted by Aedes aegypti L. mosquitoes, and the prevention of these diseases is based mainly on vector control. The use of synthetic products for this purpose has shown problems mainly related to mosquito resistance and environmental toxicity, and studies are needed to enable the development of safer and more effective products. Thus, the objective of the study was to perform the bioprospecting of larvicidal activity against Aedes aegypti of aromatic plant species of the local flora, determining the best time of collection to obtain the essential oils through the evaluation of chemical composition, biological activity, and safety against, Artemia salina Leach and Danio rerio Hamilton Buchanan from them, to obtain larvicidal bioproducts. Chapter I comprises a literature review of essential oils and isolated compounds that have been evaluated for their larvicidal activity, and safety, and it has been shown that several oils have this biological activity and safety for use in the environment, guiding future research. Chapter II presents the results of the seasonal bioprospecting of the chemical composition, larvicidal activity and toxicity of the species: Eugenia uniflora L., Lantana camara L., Plectranthus neochilus Schltr and Ocimum basilicum L.; The chemical analysis performed by chromatography coupled to mass spectrometry showed curzerene, germacrene D, caryophyllene and methylchavicol/linalool as major compounds, respectively. Although the species presented larvicidal activity against Aedes aegypti, the essential oils showed toxicity against the non-target organisms evaluated, and additional safety studies are required. Chapter III deals with the influence of seasonality on the chemical composition, larvicidal and toxicological activity of a rare chemotype of the species Cinamomum verum J. Perls, characterized by the presence of the major compound cinnamyl acetate, and despite the larvicidal activity, the essential oil showed high toxicity against non-target organisms and further safety studies are needed to validate the use of this oil in the environment. Chapter IV deals with the influence of seasonality on the chemical composition, larvicidal and toxicological activity of Mesosphaerum suaveolens (L.) Kuntze species, where GC-MS analysis showed qualitative and quantitative changes, with 1,8-cineol as the major compound in all species the evaluated times. The oils showed larvicidal activity against A. aegypti, with lethal concentrations 90.8-135.2 μg/mL, and their isolated compounds showed no activity up to the highest concentration tested, the oils also showed lower toxicity against A. salina and D. rerio, with concentrations ranging from 94.6-215.7 μg/mL, demonstrating the potential of the species essential oil for production of larvicidal bioproducts. Chapter V describes the possible mechanism of larvicidal action of the essential oil of M. suaveolens through the enzyme inhibition of Acetylcholinesterase (AChE), in addition to detailing structural changes in the larva caused by the essential oil. In the general context the bioprospecting of aromatic species showed that the oils are effective against A. aegypti larvae, that seasonality influences the chemical composition and biological activities, being the collection in the dry season more promising for most essential oils, can generate larvicidal agents to be used in the control of arboviruses.